Representasi Perempuan dalam Novel Cantik Itu Luka Karya Eka Kurniawan: Kajian Feminisme - Rati Putri Utami; Renata Marsha Aswandi; Syiva Virgginnia; Abdurahman . (CV. ITTC INDONESIA, 2026)
This study aims to examine the representation of women in the novel Cantik Itu Luka by Eka Kurniawan through a feminist perspective. The novel portrays various experiences of women related to gender inequality, including violence, bodily exploitation, and social marginalization. This research employs a qualitative method with a descriptive-analytical approach. The data consist of selected excerpts that reflect the representation of female characters in the novel. The findings reveal that women in Cantik Itu Luka are often positioned as victims within a patriarchal system; however, they also demonstrate forms of resistance, both explicit and implicit. This representation highlights the complexity of women’s roles, not only as oppressed figures but also as individuals who possess the agency to survive and resist. Therefore, the novel serves not only as a reflection of social reality but also as a critique of persistent gender inequality in society.